Diagnostic importance of immunohistochemical markers expression in differential diagnostics of classical Hodgkin Lymphoma. - Gurtovyy, V. A. (Морфологія / Morphologia / Morfologìâ, 2012)
In our study expression of the most applicable immunohistochemical markers, such as CD15, CD30, CD45 and EMA, in Hodgkin Lymphoma diagnostics were investigated in order to determine the most useful their combination. Immunoperoxidase staining of formalin-fixed paraffin embedded specimens of affected lymph nodes from 67 Hodgkin lymphoma patients were performed. Various combinations of expressions of mentioned markers by the HRS-cells, membrane and cytoplasmic staining patterns intensity were described in different types of Hodgkin Lymphoma. As were shown in the study, application all of these markers must be done for making diagnosis of Hodgkin Lymphoma. It was determined that expression by tumor cells both s+cyCD30and EMA is the pathognomonic for the diagnosis of classical forms of Hodgkin Lymphoma.